La metáfora del no-lugar (2015)
El propósito del escrito consiste en explorar la metáfora levinasiana del no-lugar,precisar sus sentidos y evaluar críticamente su pertinencia en el ámbito de las reflexiones contemporáneas. Para ello, contextualizaremos la propuesta levinasiana en torno al no-lugar, especialmente bajo los conceptos de sensibilidad, proximidad e infinito; reconstruiremos algunas de las críticas de Levinas a lo que denominamos: “filosofías del regreso a casa”; y, finalmente, sugeriremos algunos aspectos en los cuales las tesis del filósofo judío podrían hacerse pertinentes. Este último propósito lo acompañaremos con una investigación social adelantada al respecto.ABSTRACTThe purpose of this writing is to explore the Levinasian no-place metaphor, in order to clarify its meanings as well as to critically evaluate its pertinence under the light of contemporary reflections. In order to do this, we will contextualize the Levinasian proposal around the no-place, especially under the concepts of sensitivity, proximity, and infinite; we will reconstruct some Levinas’s critiques which we will call “philosophies of the coming back home”, and finally we will suggest some aspects in which the Jew philosopher theses might be pertinent. This last purpose will be accompanied by a social research carried out about this issue.